2008
DOI: 10.1345/aph.1l015
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotics and Diabetes: An Age-Related Association

Abstract: Antipsychotic drug use was associated with diabetes mellitus. This association was stronger in younger patients. In older adults, the difference was much smaller and, in some cases, there was no association. A lower risk was associated with atypical agents, as compared with typical antipsychotics. Clinicians should be aware that young adults treated with antipsychotics are at increased risk for diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 34 publications
(37 reference statements)
4
36
1
Order By: Relevance
“…Similar to many studies of healthy children, adolescents, and adults, we also found that subjects with type 1 diabetes and with antipsychotic medication had increased weight (8)(9)(10)(11)(12)(13). Interestingly, our survey showed an increased BMI with both typical and atypical antipsychotic treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to many studies of healthy children, adolescents, and adults, we also found that subjects with type 1 diabetes and with antipsychotic medication had increased weight (8)(9)(10)(11)(12)(13). Interestingly, our survey showed an increased BMI with both typical and atypical antipsychotic treatment.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to the extrapyramidal symptoms caused by typical antipsychotics, the adverse metabolic effects of atypical antipsychotics are of concern (8)(9)(10)(11)(12)(13)(14). The use of atypical antipsychotics may result in weight gain, changes in lipid concentrations, increased glucose concentrations, and insulin resistance in healthy subjects (8)(9)(10)(11)(12)(13)(14). Weight gain occurs in up to 50% of patients receiving longterm treatment for schizophrenia (8).…”
mentioning
confidence: 99%
“…The findings are consistent with results from controlled trials [25][26][27] and epidemiology studies 31 that demonstrated early onset and rapid progression of metabolic risk factors after antipsychotic treatment in children. The fact that only a few children were screened suggests that actual rates of metabolic abnormalities in these settings may be higher and that claimsbased estimates available to state policy makers may underestimate true rates of these problems.…”
Section: Commentsupporting
confidence: 89%
“…24 Relatively little information exists regarding the shortterm and long-term metabolic effects of antipsychotic use in children, 25 although initial observations indicate that metabolic adverse effects of antipsychotic treatment in pediatric populations are readily detected. [26][27][28][29][30][31] Compared with adults, children who take olanzapine, risperidone, and quetiapine fumarate are particularly at risk for weight gain. [28][29][30][31] Type 2 diabetes and cardiovascular adverse events have also been identified in children and adolescents exposed to antipsychotics, especially when multiple antipsychotics are prescribed or antipsychotics are coprescribed with mood stabilizers and antidepressants.…”
mentioning
confidence: 99%
See 1 more Smart Citation